2017
DOI: 10.1007/978-3-319-66179-7_77
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas Segmentation in MRI Using Graph-Based Decision Fusion on Convolutional Neural Networks

Abstract: Automated pancreas segmentation in medical images is a prerequisite for many clinical applications, such as diabetes inspection, pancreatic cancer diagnosis, and surgical planing. In this paper, we formulate pancreas segmentation in magnetic resonance imaging (MRI) scans as a graph based decision fusion process combined with deep convolutional neural networks (CNN). Our approach conducts pancreatic detection and boundary segmentation with two types of CNN models respectively: 1) the tissue detection step to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…In their work, they use 2D CNNs to encode the features of 3D CT volumes. Although it has been shown that for some segmentation tasks, applying 2D CNNs to 3D data can give reasonably well results as the segmentation itself can sometimes be addressed slice by slice which favors 2D operations [21], [22]. However, as denoted in [23] and also demonstrated in this work, 2D CNNs do not work well in detection problems as they cannot capture the 3D spatial information that is critical to the detection of the target object.…”
Section: Introductionmentioning
confidence: 78%
“…In their work, they use 2D CNNs to encode the features of 3D CT volumes. Although it has been shown that for some segmentation tasks, applying 2D CNNs to 3D data can give reasonably well results as the segmentation itself can sometimes be addressed slice by slice which favors 2D operations [21], [22]. However, as denoted in [23] and also demonstrated in this work, 2D CNNs do not work well in detection problems as they cannot capture the 3D spatial information that is critical to the detection of the target object.…”
Section: Introductionmentioning
confidence: 78%
“…However, CRF does reduce the standard deviation of Dice in all experiments, demonstrating its regularization capability in reducing inference variance. Cai et al (2016) use CRF to fuse mask and boundary predictions, which are separate branches off the same backbone during training, as a cascaded task that post-processes pancreas segmentation of MR Images. In this work, CRF still operates on neighbouring pixels in a feature space spanned by hand-crafted image features and the features learned by both segmentation branches.…”
Section: Locally Connected Crfmentioning
confidence: 99%
“…Nevertheless, compared to the detection and segmentation of cystic lesions, the approximate segmentation of this organ avoids demanding performance burdens. Furthermore, there exists various work focusing on segmentation of whole pancreas [11,2] and their results are good enough as an initial step for our method. Further improvement of the accuracy of our method can be achieved by including demographic information for classification [5], which will be integrated as future work.…”
Section: Discussionmentioning
confidence: 99%